The downsized hand in personal neglect. Issue 10 (25th November 2020) - Caggiano, Pietro; Veronelli, Laura; Mora, Laura; Arduino, Lisa S.; Corbo, Massimo; Cocchini, Gianna
ABSTRACT: Introduction: Personal neglect (PN) refers to a form of hemi-inattention toward the contralesional body space and it usually occurs following a right brain lesion. Recent studies suggest that PN indicates a disorder of body representation. Specifically, patients with PN show difficulties in identifying differences between left and right hands and have an altered visuospatial body map, which is associated with disrupted mental body representations. However, the metric representation of the body, and in particular the hands, has not been systematically addressed in patients showing this form of neglect. Method : In the present study, we have investigated this representation by testing the perceived hands' width of 11 hemiplegic patients with right hemisphere cerebral lesions (5 with PN) and 12 healthy controls on a judgment of passability task. Patients and controls were asked to imagine inserting their hand (left and right) through a series of vertical apertures of different sizes and to judge whether their hand could fit through. Due to the heterogeneity of the data, both parametric and non-parametric approaches were used. Furthermore, additional single-case analyses were conducted. Results : Study findings showed that patients with PN showed a significant underestimation of the left hand compared with their right hand. In contrast, whilst the right hand was equally distorted in both patients' groups, the hemiplegic patients with no evidence of PN tended to perceive the affected hand as larger than their ipsilesional one. Conclusions : In line with the literature, our findings confirm an underlying distorted body representation following right brain damage. However, for the first time, we report both a quantitative and qualitative difference in impact of hemiplegia and PN on body representation of the contralesional body space.